PROSPECTS OF BEE-BOT APPLICATION IN THE EDUCATIONAL PROCESS - Лусте, Ірина; Яшан, Богдан; Пукальський, Іван (SWorldJournal, 2022)
This article examines the features of the use of Bee-Bot in the educational process. The main functions of working with the Bee-Bot mini-robot are analyzed. The expediency of using special thematic field-routers and their impact on children’s development